(untitled) (Annals of Medical Research, 2024)
Aim: In this study, it was aimed to determine the sociodemographic characteristics, childhood traumas, alexithymia and coping methods with stress in women exposed to intimate partner violence and to examine the relationship between these characteristics and intimate partner violence in comparison with women who were not exposed to violence. Materials and Methods: The study included 42 women who had been exposed to intimate partner violence in the last year and 42 women as the control group who applied to the Behavioral Sciences Center in our center. Sociodemographic data form, DSM-5 oriented diagnostic interview guide, Toronto Alexithymia Scale (TAS), Childhood Trauma Scale (CTS) and Stress Coping Styles Scale (SCS) were applied to all participants and the data obtained were compared. Results: The rates of income level, education level of the partner and employment status of the partner were lower in the case group compared to the control group, while the rates of divorce, separation, elopement, forced marriage, witnessing domestic violence in childhood and inflicting violence on their children were higher in the case group. It was found that 97.6% of the women in the case group had experienced recurrent violence and 33.3% had been subjected to violence in their past relationships. Significant differences were found between the groups in the total scores of the TTS, the total scores of the CFTQ, and the scores of the SBTQ. There was a relationship between alexithymic characteristics and preferred stress coping methods. Alexithymia and childhood traumas were found to have a predictive effect on partner violence. Conclusion: The fact that the level of alexithymia and the use of ineffective methods to cope with stress are higher in women who are victims of violence is important in therapeutic studies to be conducted with these women. Variables affecting intimate partner violence should be evaluated in a larger population with longitudinal follow-up.